Internationalization of higher education: A study with fellows students of a higher education institution in Brazil - Sena, Andrelina Pimentel de; Matos, Fátima Regina Ney; Machado, Diego de Queiroz; Sena, Augusto Marcos Carvalho de (Education Policy Analysis Archives, 2014)
The central theme of this research is the internationalization of education, focusing on the experience of students engaged in academic exchange programs. Our goal was to investigate the implications of participation in international academic exchanges in the process of qualifying students. Thus, this research followed the line of other studies carried out, opting to focus its analysis of the issue of internationalization of higher education institutions in a Brazilian university, in this case the University of Fortaleza (UNIFOR), which participates in academic exchange programs with international education institutions. In short, the data collected showed that the difficulties encountered by exchange students from Brazil and abroad were related to communication, since most students are not considered fluent in the language of the country of arrival. Significant differences were noted in the education system. Differences were considered beneficial for both academics and professionals. In the perception of Brazilians, the teacher-student relationship is characterized by formalism. Familiarity with local culture was common to Brazilians and foreigners. The experience of participating in the exchange was considered excellent and good for all students.